ADMINISTRATIVE AND TECHNICAL CONSTRAINTS OF ELECTRONIC ADMINISTRATION AND THEIR IMPACT ON THE EFFECTIVE MANAGEMENT OF SPORTS ADMINISTRATION IN ALGERIA - Imed Delhoum; Allaoua Samir (International Journal of Innovative Technologies in Social Science, 2025)
Change has become a characteristic feature of the civilisational dimension of the developed world, necessitating the monitoring of all transformations occurring within the environment surrounding both individuals and organisations to confront the consequences of such change and keep pace with new developments. In this context, organisations must adopt and utilise the most advanced administrative methods, in line with technological advancements and in response to the digital age and information technology. Among these methods is electronic administration (E-Management), a contemporary concept that has emerged in recent years as a result of the increasing use of computers and networks and the information revolution in general. Electronic administration represents a strong response to the challenges of the twenty-first century, an era defined by globalisation, knowledge, and the dynamics of the internet revolution. Most administrations worldwide, in general, and sports administrations in particular, have responded to this transformation according to their specific conditions, capacities, and circumstances. In recent years, there has been rapid and significant development in information and communication technology across multiple levels, with a profound impact on human behaviour, methods, and approaches to administration. Consequently, many organisations, including those in both developed and developing countries, such as Algeria, have begun to adopt the concept of electronic administration. This transition has been made evident through the dissemination of information via the internet, as well as the conduct of numerous internal transactions through the internet and intranet. These networks have provided sports organisations and their clients with opportunities for communication beyond intricate bureaucratic procedures. Notably, the application of electronic administration in the sports field has achieved remarkable success across various organisations worldwide. However, the situation in China is distinct. Despite the rapid progress in information technology, many challenges and obstacles persist, hindering its application as a means to facilitate management processes and enhance effectiveness. Within this framework, our study addresses the following topic: "Administrative and Technical Constraints of Electronic Administration and Their Impact on the Effective Management of Sports Administration in Algeria." The study aimed to identify the most significant administrative constraints that hinder the effective management of electronic administration within Algerian sports organisations and to highlight the technical and human obstacles impeding its application in these organisations. Among the key findings of the study are that the reliance of the Algerian sports administration on traditional management methods has delayed the transformation towards a smooth and efficient application of electronic administration. The technical constraints identified include the limited development of the infrastructure required to implement electronic administration in sports management; the difficulty experienced by sports organisations’ administrators in Algeria in keeping pace with the rapid global changes and advancements in information technology; and the absence of security systems to safeguard databases related to management processes within sports organisations. The study also revealed several human constraints, including the lack of specialised training and development programmes dedicated to enhancing the capacities of human resources in Algerian sports administration, to master modern electronic technologies necessary for the successful implementation of electronic administration. Additional constraints included the absence of a culture of change among those responsible for managing Algerian sports organisations, as well as the shortage of qualified personnel specialising in maintaining electronic equipment, devices, and management-related software at various administrative levels.